Das dialektische Verhältnis von Theorie und Praxis in der Pädagogik - Schmied-Kowarzik, Wolfdietrich (Kassel University Press, 2008)
"The Dialectical Relationship between Theory and Practice in Education" relies on the book of Schmied-Kowarzik on dialectical pedagogy ("Dialektische Pädagogik") which was inspired by Hans Rauschenberger and originally published in 1974. In the present volume the author tries to bring clarification into the former philosophical and pedagogical debate with its different use of the term "dialectic".